2023
DOI: 10.1007/s00170-023-11227-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heat source arrangement on coupling characteristics of low-power pulsed laser-MAG hybrid welding

Abstract: Low power pulsed laser-MAG hybrid welding was carried out by different heat source arrangement methods (lead mode, distance between laser spot and welding wire tip (DLA)). The coupling effect and welding characteristics of hybrid heat sources under different modes were studied by using high speed image (HSI) and real-time electrical signals. HSI observation and electronic signals showed that the lead mode and DLA significantly affect the coupling state of heat source and welding characteristics (weld morpholog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The results showed that welding current considerably influenced the length of arc and the transition mode of droplets. Tao et al [11] used different heat source arrangement methods and carried out Laser-MAG hybrid welding tests on 6-mm thick Q345 steel plates. The laser energy distribution on the welding wire could be optimized by adjusting the wire spacing; when the filament spacing was 1-2 mm, a good weld was obtained.…”
Section: Several Contemporary Scholars Have Undertaken Substantial Ex...mentioning
confidence: 99%
“…The results showed that welding current considerably influenced the length of arc and the transition mode of droplets. Tao et al [11] used different heat source arrangement methods and carried out Laser-MAG hybrid welding tests on 6-mm thick Q345 steel plates. The laser energy distribution on the welding wire could be optimized by adjusting the wire spacing; when the filament spacing was 1-2 mm, a good weld was obtained.…”
Section: Several Contemporary Scholars Have Undertaken Substantial Ex...mentioning
confidence: 99%